Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kinerja Pemasaran dengan Penetrasi Pasar dan Inovasi Produk Sebagai Variabel Intervening (Studi pada Usaha Ekspedisi ) - Pati Ritan, Patrianus; Yoestini (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study investigates the influence of service quality and product quality on marketing performance, with market penetration and product innovation serving as intervening variables in expedition companies. Guided by the Service-Dominant Logic (SDL) framework, the research underscores the role of value co-creation between companies and customers in driving competitive advantage. Using a quantitative approach, data were collected from employees involved in operational and marketing functions and analyzed through Structural Equation Modeling (SEM). The findings indicate that service quality and product quality do not significantly affect market penetration. Conversely, market penetration positively influences product innovation, which in turn strongly enhances marketing performance. However, when not managed effectively, market penetration can negatively impact marketing performance. These results highlight the need for companies to adopt integrated and innovative strategies that align with customer value creation to achieve sustainable improvements in marketing performance within the expedition industry.